Kitchen Waste Residues asKitchen Waste Residues as Potential Renewable Biomass Resources for the Production of Multiple Fungal Carbohydrases and Second Generation Bioethanol - Janveja, Chetna; Rana, Susheel Singh; Soni, Sanjeev Kumar (Journal of Technology Innovations in Renewable Energy, 2013)
Utilization of kitchen waste, the major portion of municipal solid waste for the coproduction of multiple carbohydrases and bioethanol was investigated in this study. Solid-state fermentation was performed to evaluate the potential of various steam pretreated kitchen waste residues as substrates for the coproduction of cellulolytic, hemicellulolytic, pectinolytic, amylolytic enzymes by a locally isolated strain of Aspergillus niger CJ-5. All the kitchen waste residues simply moistened with water, without the supplementation of exogenous nutrients proved good for the induction of all the enzyme components of a cocktail after 96 h incubation. Of all the substrates evaluated, steam pretreated potato peels induced maximum yields corresponding to 69.0±1.92U CMCase, 16.5±0.54U FPase, 44.0±1.28U β-glucosidase, 999.0±28.90U xylanase, 58.2±2.12U mannanase, 120.0±3.72U pectinase, 31520.0±375.78U α-amylase, 482.8±9.82U glucoamylase/g dry substrate (gds). Saccharification of residues using inhouse produced crude enzyme cocktail resulted in the release of 610±10.56, 570±8.89, 435±6.54, 475±4.56, 445±4.27, 385±4.49, 370±6.89, 490±10.45 mg of total reducing sugars/g of dried potato peels, orange peels, pineapple peels, mausami peels, onion peels, banana stalks, pea pods and composite mixture respectively revealing carbohydrate conversion efficiencies in the range of 97.0-99.4%. After fermentation of released hexoses, alcohol yields ranging from 80±1.069 - 262±7.86 µL/gds were obtained.